Rancang Bangun Inkubator Anak Ayam Doc (Day Old Chick) Otomatis Berbasis Mikrokontroler - Moh Supriyanto (Universitas Islam Lamongan, 2020)
Indonesia is a country where many residents have livestock. Starting from raising chickens, ducks, goats and cows. In the care of chicks, special care is needed, because newborn chicks are vulnerable to disease, thus inhibiting the rate of growth. The problem that is often faced by breeders is the temperature conditions that exist in the cage only by entering the temperature detector into the cage, and adjust the heater manually. For this reason, microcontroller-based chicks incubators are made. This tool is expected to help the chicken farmers to check the temperature conditions in the cage and can adjust the heater automatically to maintain the temperature stability of the incubator room. To regulate the temperature in the cage to remain stable by turning on, dimming and turning off lights and fans automatically, so that in the growth of chicks are not susceptible to disease due to instability of the cage's temperature. By using the dht11 sensor as a temperature and humidity detector, this tool can be used for three types of Doc chicks namely broiler chickens, broilers & native chickens, in turn. From several tests that have been carried out this tool has managed to stabilize the temperature of the cage by 75% and the average success of using chicks by 80% that survive.